Family violence : legal, medical, and social perspectives - Wallace, Harvey (Routledge, 2016)
Family Violence: Legal, Medical, and Social Perspectives examines the entire spectrum of family violence, focusing on social processes and social relationships. The eighth edition is a multidisciplinary introduction to the study of domestic violence that guides readers to a better understanding of the challenges involved in reducing or eliminating violence. The new edition includes more information on PTSD and head trauma, a new section in children witnessing domestic violence, more international perspectives, which allow students to understand that family violence crosses borders and cultures, and a series of Promising Practices boxes that bring professional knowledge and accomplishments into the classroom.